Assessing the Walkability Environments of Churches in a Rural Southeastern County of the United States. Issue 1 (January 2022) - Bernhart, John A.; Wende, Marilyn E.; Kaczynski, Andrew T.; Wilcox, Sara; Dunn, Caroline G.; Hutto, Brent
Abstract : Context: Churches can serve as important health promotion partners, especially in rural areas. However, little is known about the built environment surrounding churches in rural areas, including how these environments may impact opportunities for physical activity (PA) and may differ by neighborhood income levels. Objective: This study described walkability around churches in a rural county and examined differences in church walkability between high-, medium-, and low-income neighborhoods. Design: As part of the Faith, Activity, and Nutrition study, trained data collectors conducted a windshield survey of adjacent street segments within a half-mile of churches. Setting: Churches (N = 54) in a rural southeastern county in the United States. Main Outcome Measure: A summary walkability score (eg, presence of sidewalks, safety features, low traffic volume) was created with a possible range from 0 to 7. Analysis of variance was used to assess differences in walkability of churches by neighborhood income levels. Results: Walkability scores ranged from 0 to 6 ( M = 2.31, SD = 1.23). Few churches had sidewalks, shoulders or buffers, or amenities nearby. In contrast, most churches had low traffic volume and no environmental incivilities. While not statistically significant, churches in low-income neighborhoods scored higher for walkability than churches in medium- and high-income neighborhoods. Conclusions: This study used low-cost environmental audits to analyze walkability in a sample of churches in a rural area and examined differences by neighborhood income. While churches may improve reach of people living in underserved and rural communities, a lack of environmental supports may limit effective PA promotion activities. Partnerships focused on improving existing areas or providing alternative PA opportunities for church and community members may be needed, especially in African American communities.